The role of transformational leadership and organizational culture on innovative behavior : A Review - Zulkifli Musannip Efendi Siregar (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2024)
Transformational leadership has an impact on the work behavior of the apparatus. Leaders who are able to provide enthusiasm, are able to inspire the apparatus, will make the apparatus comfortable in working and ultimately innovative work behavior occurs in work activities. A good work culture also creates a comfortable and conducive work atmosphere, so that employees will be more innovative in working